2022
DOI: 10.1186/s13063-022-06672-4
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual health interventions, schooling, and mental health problems among Ugandan students (MENISCUS): study protocol for a school-based cluster-randomised trial

Abstract: Background Menstrual health is an increasingly recognised public health issue, defined as complete physical, mental, and social well-being in relation to the menstrual cycle. The MENISCUS trial aims to assess whether a multi-component intervention addressing physical and emotional aspects of menstrual health improves educational attainment, mental health problems, menstrual management, self-efficacy, and quality of life among girls in secondary school in Uganda. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Menstrual knowledge is hypothesised to improve girls’ MH and reduce negative psychosocial consequences such as distress. 5 , 53 , 54 , 55 No included studies assessed broader outcomes although they have been included in trials of MH interventions in other regions, such as a menstrual health trial in Uganda which included mental health and quality of life outcomes 55 , 56 In the present review, interventions tested to improve MH knowledge were small-scale training initiatives delivered outside of formal education systems to school-aged females, and to a lesser extent, female university students. This differs from progress in the region, 9 where our regional review of practice identified progress in policy objectives for MH education taught through school curriculums.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Menstrual knowledge is hypothesised to improve girls’ MH and reduce negative psychosocial consequences such as distress. 5 , 53 , 54 , 55 No included studies assessed broader outcomes although they have been included in trials of MH interventions in other regions, such as a menstrual health trial in Uganda which included mental health and quality of life outcomes 55 , 56 In the present review, interventions tested to improve MH knowledge were small-scale training initiatives delivered outside of formal education systems to school-aged females, and to a lesser extent, female university students. This differs from progress in the region, 9 where our regional review of practice identified progress in policy objectives for MH education taught through school curriculums.…”
Section: Discussionmentioning
confidence: 99%
“…Trials in other geographic regions (Sub-Saharan Africa, South Asia) have trialled product provision including but not limited to school attendance, wellbeing, and reproductive health including urogenital infection, with mixed results to date. 5 , 7 , 55 All interventions that tested product provision included reusable menstrual products, reflective of the growing attention to reusables and environmental sustainability. 9 , 62 …”
Section: Discussionmentioning
confidence: 99%
“…Trials using the MPNS measures as primary or secondary outcomes will provide insights into the sensitivity of the measure to change and use for evaluation. [8,12] Finally, future research should investigate the validity of the shorter MPNS forms in new cultural contexts, languages and age groups. As found previously, [6] the dimensionality of the MPNS-36 differs for adult women, and we would hypothesise similar differences for the short form.…”
Section: Implications For Research and Practicementioning
confidence: 99%
“…[1,2] The Menstrual Practice Needs Scale (MPNS-36) [3] was published in 2020 to address this gap and has seen rapid uptake in research and practice. [4][5][6][7][8][9][10][11][12] However, this comprehensive scale is 36-items in length, presenting a barrier to implementation in short needs assessments or multicomponent surveys. Stakeholders have requested a short form to enable greater uptake.…”
Section: Introductionmentioning
confidence: 99%
“…The intervention addressed health promotion (education, attitudes, well-being) and goods (menstrual products, improved WASH facilities, pain management), and was feasible to deliver and highly acceptable to stakeholders. This led to development of a cluster-randomised trial in 60 secondary schools in Wakiso and Kalungu districts to evaluate the effectiveness of the MENISCUS intervention on education, health and wellbeing outcomes [ 9 ].…”
Section: Introductionmentioning
confidence: 99%